Increasing Antenatal Care (ANC) Visits through Education for Pregnant Women at the Gurah Community Health Center, Kediri Regency - Reni Yuli Astutik; Marminingsih; Endang Dwiwati (Journal of Community Engagement in Health, 2025)
Quality antenatal care is a key factor in ensuring pregnant women are prepared for a safe delivery and in preventing complications that require special medical attention. Low attendance at antenatal visits is partly due to a lack of awareness about the importance of timely ANC check-ups. To improve the quality of antenatal visits among pregnant women at Gurah Public Health Center, Kediri Regency. This community service activity was conducted for pregnant women in the Gurah Public Health Center area from September 30 to October 30, 2024, with 10 pregnant women in the first trimester. The activity consisted of three stages: preparation, implementation, and evaluation. The findings showed that after receiving education, there was an increase in pregnant women’s knowledge regarding antenatal visits. Education can enhance the participation of pregnant women, which is expected to improve the coverage of ANC services in accordance with the set targets.